Enterprise security : a data-centric approach to securing the enterprise : a guide to applying data-centric security concepts for securing enterprise data to enable an agile enterprise /: a data-centric approach to securing the enterprise : a guide to applying data-centric security concepts for securing enterprise data to enable an agile enterprise. (2013) - Unknown
No abstract available